The Effect of Carbonated, Isotonic, and Yoghurt Drinks to the Hardness of Bulk Fill Composite Resin - Tyagita Haning Ratnasari; Nadia Hardini; Yoghi Bagus Prabowo; Faizah Fulyani (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Composite resin often used as a restoration material due to its advantages in the aesthetic field. The bulk-fill type is one of the composite resin that can be applied directly into cavities as deep as 4 mm, so that restoration procedure becomes easy and effective. Hence, exposure to various acidic drinks can reduce the hardness of composite resins and eventually lead to failure of the tooth restoration process.Objective: This research aimed to evaluate the effects of several commercial acidic drinks, (carbonated, isotonic, and yogurt) on the hardness of bulk-fill composite resins.Method: This research was an experimental study with a post-test control group design. Twenty-four specimens were made with the size 10 x 4 mm using the metal mold rings. Specimens were divided into 4 groups for artificial saliva (served as a control), carbonated, isotonic, and yogurt. Specimens were immersed in storage agents for 5 seconds followed by artificial saliva for 5 seconds. This cycle was repeated 20 times for 14 days. The bulk-fill composite resin hardness was measured using a Micro Vickers Hardness Tester with a load of 100 grams for 10 seconds. Statistical analysis was performed using One Way ANOVA and Post Hoc LSDResults: Data were normally distributed and homogeneous with p > 0.05. The One Way ANOVA test showed the biggest difference in bulk fill composite resin between 4 groups (p < 0.001). The Post Hoc LSD test showed significant differences between all groups (p < 0.001)Conclusion: Carbonated, isotonic, and yogurt drink significantly decreased surface microhardness of bulk-fill composites resin but the carbonated drinks greatly reduce the hardness value since it has the lowest pH of 2.3.